Implementation of Strengthening the Character of Mutual Cooperation through Habituation of Clean Friday Activities - Sri Wahyuningsih; Muhamad Sholeh; Karwanto Karwanto (International Journal of Education, Language, and Religion, 2025)
the role of education is a crucial role in shaping the personality of the younger generation. There are various types of character education that can be given to students from an early age, one of which is gotong royong. According to the results of the analysis explained in strengthening the unity of the Indonesian nation and the formation of social identity there is a cultural heritage known as gotong royong. However, along with the development of this world, the values of gotong royong began to disappear, especially among the younger generation. The purpose of the writing is to provide analysis results related to the implementation of strengthening the character of mutual cooperation through the habituation of clean Friday activities. The research method used in this writing adopts qualitative research methods. The results of the research findings are that the clean Friday activities carried out in almost all schools have the aim of shaping the character of students, especially in strengthening the character of mutual cooperation. The clean Friday culture implemented at the basic education level can be done in various ways including cleaning the school yard, throwing garbage in its place, providing a clean bathroom, having a place to wash hands, and providing a garbage disposal. The conclusion drawn is that the activities in Clean Friday are not only based on cleaning activities. But it can also foster and strengthen the character of mutual cooperation.